Analisis Strategi Pemasaran Terhadap Kepuasan Pelanggan Kopi Sumatra (Studi Kasus Kopi Sumarya) - Harthawan, I Gusti Ngurah Putra; Arwana, Oky (KRISNA: Kumpulan Riset Akuntansi, 2024)
This study aims to determine the effect of the marketing mix on customer satisfaction. This research was conducted on Sumarya coffee. The number of samples specified is as high as 90 respondents. Measurement in the questionnaire using a Likert scale. Statistical data analysis is used to: a) test research instruments through the validity test and reliability test; b) perform the classical assumption test; c) perform descriptive statistical analysis using the frequency distribution; and d) perform statistical analysis using multiple regression analysis with the help of the SPSS 20 program. The results of hypothesis testing show that there is a significant direct positive effect between products on customer satisfaction, with an unstandardized beta coefficient value of 0,382 and a significance of 0,000. There is a direct and significant positive effect of prices on customer satisfaction, with an unstandardized beta coefficient of 0,124 and a significance of 0,002. unstandardized beta coefficient value of 0,013 with a significance of 0,008. The results of this study indicate that the multiple regression analysis shows a positive and significant direct effect of customer decisions on the level of sales.